Role of lung ultrasound patterns in monitoring coronavirus disease 2019 pneumonia and acute respiratory distress syndrome in children - Satyabrata Roychowdhoury; Subhajit Bhakta; Manas Kumar Mahapatra; Saptarshi Ghosh; Sayantika Saha; Mithun Chandra Konar; Mihir Sarkar; Mousumi Nandi (Clinical and Experimental Pediatrics, 2022)
Background During the coronavirus disease 2019 (COVID-19) pandemic, lung ultrasonography (US) has been gaining importance in pediatric intensive care and emergency settings for the screening, diagnosis, and monitoring of pulmonary pathology. Purpose To describe the pattern of lung US changes in patients with COVID-19 pneumonia and its potential role in monitoring ventilated patients. Methods This prospective observational study included children aged 1 month to 12 years with a confirmed diagnosis of COVID-19. Lung US was performed using a high-frequency linear probe (5–12 MHz) in all children with moderate/severe respiratory symptoms within 24 hours of admission and then daily until the patient required oxygen therapy. Lung involvement severity was assessed using lung US scores, while lung aeration improvement or deterioration was measured using lung ultrasound reaeration scores (LUSReS). Results Of 85 children with moderate to severe disease, 54 with pulmonary disease were included. Of them, 50 (92.5%) had an interstitial pattern, followed by pleural line abnormalities in 44 (81.5%), reduced or absent lung sliding in 31 (57.4%), and consolidation in 28 (51.8%). A significantly higher lung US score (median, 18; interquartile range [IQR], 11–22) was observed in ventilated versus nonventilated patients (median, 9; IQR, 6–11). LUSReS improvement after positive end-expiratory pressure titration was positively correlated with improved dynamic lung compliance and oxygenation indices and negatively correlated with the requirement for driving pressure. Successful weaning could be predicted with 100% specificity if loss of LUSReS ≤ 5. Conclusion Interstitial syndrome, fragmented pleural line, and subpleural microconsolidation were the most prevalent lung US findings in children with COVID-19 pneumonia. Thus, lung US may have the ability to monitor changes in lung aeration caused by mechanical ventilation and predict its successful weaning in children with COVID-19.